Soliton dynamics in passively mode-locked fiber lasers - Zhao, Luming (2008)
Due to their compact structure, convenient collimation, flexible design, and improving pulse intensity, fiber lasers have attracted more and more attentions as a simple inexpensive ultrashort pulse source in many scientific fundamental researches and various applications. This thesis presents a comprehensively experimental and theoretical study of nonlinear dynamics of the passively mode-locked fiber lasers. It is shown numerically that the formation of multiple solitons in the lasers is caused by a peak power limiting effect of the laser cavity. And the soliton energy quantization observed is a natural consequence of the gain competition between the multiple solitons. Multi-pulse solitons were observed in a dispersion-managed fiber laser. For the first time, we have observed soliton period-doubling bifurcations and complete period-doubling route to chaos in the fiber lasers. Noise-like pulse emission was also revealed. A self-started high-repetition-rate soliton fiber laser that could generate 100GHz soliton pulse train is built up.